Rabies response, One Health and more-than-human considerations in Indigenous communities in northern Australia. (September 2018) - Degeling, Chris; Brookes, Victoria; Lea, Tess; Ward, Michael
Abstract: Australia is currently canine rabies free; however, the spread of rabies in eastern Indonesia poses an increasing risk to northern Australia. Domestic dogs are numerous in East Arnhem Land (EAL) and the Northern Peninsular Area (NPA), usually unrestrained and living in close relationships with humans. The response to any rabies outbreak on Australian territory will focus on dog vaccination, controlling dog movements and depopulation. A One Health approach to zoonotic disease control should seek to co-promote human and animal health, whilst also seeking to accommodate the preferences of affected communities. We report on 5 collaborative workshops and 28 semi-structured interviews conducted between January 2017 and June 2018 with: (i) EAL and NPA community members; (ii) Indigenous Rangers in EAL and NPA; and (iii) residents of Cairns, the local regional centre. Storyboard methodologies were used to work with participants and explore what rabies response measures they thought were justified or unacceptable, why they held these views, and what other steps they believed needed to be taken. Key findings include that the capacity of the NPA and EAL communities to contribute/adapt to a biosecurity response is limited by structural disadvantage including poor infrastructure (such as lockable premises and intact fences) and appropriate information, dominant cultural norms and food security concerns. Dogs and dingoes can have great cultural and social importance; key interventions might be accommodated within cultural beliefs and long-standing norms of dog management if sufficient effort is made to adapt interventions to local contexts and community preferences. Adopting such a 'strengths-based' approach mandates that the communities at greatest risk need help to prepare for and develop strategies to manage a biosecurity response to a rabies incursion. This would include listening to individual and community concerns and attending to the educational and infrastructural needs for supporting different groups to respond appropriately. Highlights: Focuses on Indigenous perspectives in a policy framework for rabies control. Storyboard methods were used to exchange information on outbreak risks and impacts. Material disadvantage is a larger barrier to policy compliance than cultural belief. One Health must be sensitive to but careful not to reify cultural difference.